What's the matter with the Dobsons? - Colman, Hila. (New York Crown Publishers, 1980)
The Dobson family seems to be coming apart as anger becomes the prevailing emotion between father and daughter and husband and wife.
Keywords: Fathers and daughters -- Fiction; Family problems -- Fiction